Diversity of edible insects in a Natural World Heritage Site of India: entomophagy attitudes and implications for food security in the region - Arup Kumar Hazarika; Unmilan Kalita; Subhash Khanna; Tarali Kalita; Sangeeta Choudhury (PeerJ, 2020)
Insects not only play a significant role in the ecological process of nature but since pre-historic times have also formed a part of the human diet. With a still growing population and skewed demographic structures across most societies of the world, their role as nutrient-rich food has been increasingly advocated by researchers and policymakers globally. In this study, we examine the edible insect diversity and entomophagy attitudes of ethnic people in Manas National Park, a UNESCO Natural World Heritage Site, located in Assam (India). The study involved a field investigation through which the pattern of entomophagy and the attitude towards insect-eating was studied. Following this, we examined the edible insect diversity and abundance at different sampling points. A total of 22 species of edible insects belonging to fifteen families and eight orders were recorded from different habitat types. Out of these 22 species, Orthopterans showed a maximum number of eight species followed by Hymenoptera (four), Hemiptera (three), Lepidoptera (two), Blattodea (two) and one species each from Coleoptera, Odonata, and Mantodea. Dominance, diversity, and equitability indices were computed along with the relative abundance of the insects concerning four habitat types. Aspects of the economic significance of entomophagy were also observed during the field investigation. To manage insects in the interest of food security, more attention should be given to sustainable collecting and rearing methods emphasizing their economic, nutritional, and ecological advantages.